2022
DOI: 10.3390/molecules27175650
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Low Doses of Ketamine and Melatonin in Combination Produce Additive Neurogenesis in Human Olfactory Neuronal Precursors

Abstract: Melatonin (MEL), an indolamine with diverse functions in the brain, has been shown to produce antidepressant-like effects, presumably through stimulating neurogenesis. We recently showed that the combination of MEL with ketamine (KET), an NMDA receptor antagonist, has robust antidepressant-like effects in mice, at doses that, by themselves, are non-effective and have no adverse effects. Here, we show that the KET/MEL combination increases neurogenesis in a clone derived from human olfactory neuronal precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…However, there is limited research exploring the relationship between EGF and neurogenesis in depression. One study shown that FGF, EGF, BDNF, ketamine, melatonin and the ketamine/melatonin combination stimulate neurogenesis and cell cluster formation in cultured human olfactory neuronal precursors, thus offering insights into the mechanism underlying their antidepressant effects (48). Once EGF binds to its receptor, EGFR, it forms a homodimer, which undergoes autophosphorylation in the intracellular kinase domain, activating signaling cascades within the cell and even in the nucleus (49).…”
Section: Egf/egfr Neurogenesis and Depressionmentioning
confidence: 99%
“…However, there is limited research exploring the relationship between EGF and neurogenesis in depression. One study shown that FGF, EGF, BDNF, ketamine, melatonin and the ketamine/melatonin combination stimulate neurogenesis and cell cluster formation in cultured human olfactory neuronal precursors, thus offering insights into the mechanism underlying their antidepressant effects (48). Once EGF binds to its receptor, EGFR, it forms a homodimer, which undergoes autophosphorylation in the intracellular kinase domain, activating signaling cascades within the cell and even in the nucleus (49).…”
Section: Egf/egfr Neurogenesis and Depressionmentioning
confidence: 99%